Pengaruh Konseling Individu Terhadap Internalisasi Nilai Islam Untuk Pecandu Narkoba - Fadilah, Annisa; Mutaqin, Zaenal; Lukman, Dede (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The purpose of the research conducted at Inabah 2 Putri is to find out how much influence individual counseling has on drug addicts, to find out how much influence the internalization of Islamic values has on drug addicts, and to find out how much influence individual counseling has on the internalization of Islamic values for drug addicts. The framework of thought used is individual counseling, internalization of Islamic values and drug addicts. Quantitative method with experimental approach. The results of the study show that 22% is the result of the influence of individual counseling (X1) on drug addicts. Furthermore, 19.2% is the result of the influence of internalizing Islamic values (X2) on drug addicts. And 19.2% is the result of the influence of individual counseling (X1) in the internalization of Islamic values (X2) against drug addicts.